The General Theory of Short-Term and Long-Term Costs - Ioan, Gina (Acta Universitatis Danubius. Œconomica, 2023)
The theory of costs is of particular importance in the theory of the producer, giving essential information on the level of production that must be achieved within the limits of acceptable costs in the market. The axiomatic approach to this theory highlights the essential aspects that are rigorously demonstrated and that provide insight into the behavior of different types of costs.